Formation of Internal Statistics of Machine Building Enterprises under the Ierarchic System of Expenditure Centers - Veriga, Yustyna; Koba, Ðžlena; ÐœÐ°tiushina, Yuliya; Myronova, Yuliya (International Journal of Engineering and Technology, 2018)
In the article it is analyzed the existing approaches to providing company management with cost information from the centers of responsibility. An algorithm for the formation of internal reporting indicators at the machine-building enterprises is proposed. The first stage of such an algorithm is the development of information cards with a list of quantitative and cost data and a schedule of workflow for each center of responsibility. Further, the established timeliness is formed by reporting and determined by the comparison of actual indicators from the estimate. Thus, account is taken of responsibility on the principle of controlling costs, which implies the spread of responsibility of each specific manager only to those areas that he can really affect. The next step is to submit forms of reporting by the heads of production units in a hierarchical scheme. The form of the reports and their content depends on the characteristics of the center of responsibility and indicators. Application of the proposed reporting will provide managers at all levels with the necessary information on the costs of the centers of responsibility, which will increase the profitability of both separate segments of activity and machine building enterprises in general.Â